Airport site selection using multiple-criteria decision analysis - the case of new Lisbon airport - Russu, Andriy (2021)
Current Lisbon Airport has been considered for many years as not corresponding to future demand expectations. The last 60 years have been marked by Portuguese government uncertainty and inconsistency and heated debate about a New Lisbon Airport location. This work is focused on airport site selection using multiple-criteria decision analysis applied to the case of New Lisbon Airport. The main objective is to apply a new methodology to the solving of this problem. Results show how the options studied performed on different aspects and what is the preferred location that best suits the necessity for an international airport in Portugal.